Ethics in accounting: A dire necessity for practicing accountants in Bangladesh - Ahmad, Afzal (IIUC Studies, 2022)
The study aims to critically examine the determinants of accounting ethics by practicing accountants as well as professional accountants working in Bangladesh. In addition, the study identifies the major factors affecting the ethical behavior of accountants. Using a 5-point Likert scale, the study collects primary data from a total sample of 110 respondents consisting both academicians and practitioners. The results revealed that there is a significant variation in the opinions regarding ethics between accounting academicians and practitioners. The majorities of the academicians have a high positive attitude toward professional ethics and perceive the afraid of creator, responsibility, accountability, objectivity, integrity, confidentiality and patience as the important determinants of accounting ethics. On the other hand, the practitioners view accountability, responsibility, transparency brotherhood, truthfulness, mutual trust, objectivity and integrity as the crucial determinants of ethics. However, both groups emphasized an ethical code of conduct, individual factors, moral development, personal value, environmental influence, peer influences, life experiences, and situational factors for accounting ethics. The findings of the study provide valuable insights to academicians, accounting practitioners, and policymakers in improving the code of professional ethics in Bangladesh. IIUC Studies Vol.18, December 2021: 47-64